2014
DOI: 10.1074/jbc.m114.600775
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-activated Receptor-α-mediated Transcription of miR-199a2 Attenuates Endothelin-1 Expression via Hypoxia-inducible Factor-1α

Abstract: Background: Elevated plasma levels of PlGF are associated with increased endothelin-1 and pulmonary hypertension (PH) in SCD. Results: miR-199a2, which targets HIF-1␣ mRNA, located in host gene DNM3os is co-transcriptionally regulated by PPAR␣. Conclusion: PPAR␣ agonist induction of miR-199a2 reduced ET-1 levels. Significance: PPAR␣ agonist reduction of ET-1 levels via induced miR-199a2 provides an alternative strategy to ameliorate PH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
74
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(79 citation statements)
references
References 48 publications
(71 reference statements)
5
74
0
Order By: Relevance
“…It has been shown that miR-199 can target HIF-1α, leading to reduced endothelin-1 expression. 40 It would be interesting to investigate whether a miR-199 and miR-214 knockout mouse would have a more pronounced PAH phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that miR-199 can target HIF-1α, leading to reduced endothelin-1 expression. 40 It would be interesting to investigate whether a miR-199 and miR-214 knockout mouse would have a more pronounced PAH phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a polymorphism in the 3′ UTR in the fibrinogen-α gene (FGA) that affects the binding of miR-759 has been associated with CTEPH (87) and pulmonary embolism. In the case of PH associated with sickle cell disease, miR-199a was reported to reduce HIF-1α expression (59). In perhaps a related context, placental growth factor (PIGF), which is upregulated in sickle cell anemia and may play a key role in promoting PH, has been associated with alterations in miR-648 (75) and the HIF-dependent and PPARα-dependent miR-301a/454 family (88).…”
Section: Divergence Of Ph-relevant Mirna Activity Among Human Diseasesmentioning
confidence: 99%
“…This locus is located within an intron of DNM3 and is transcribed from the opposite strand, hence, its designation. Transcription of DNM3os and of cotranscribed miR-199a2/miR-214 is greatly attenuated by PlGF, thus allowing unhindered expansion of HIF-1␣ activity and expression of genes, i.e., the ET-1 and PAI-1 genes, requiring this transcription factor, (18). However, the molecular mechanism of PlGF-mediated downregulation of miR-199a2/miR-214 and DNM3os ncRNA is not fully understood.…”
mentioning
confidence: 99%
“…Moreover, we have shown that posttranscriptional regulation of ET-1 and PAI-1 is achieved by microRNA 199a2 (miR-199a2), which targets the 3= untranslated region (UTR) of HIF-1␣ mRNA (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation